2011
DOI: 10.4137/cmc.s6677
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Dronedarone in the Treatment of Atrial Fibrillation/Flutter

Abstract: Dronedarone is an amiodarone analog but differs structurally from amiodarone in that the iodine moiety was removed and a methane-sulfonyl group was added. These modifications reduced thyroid and other end-organ adverse effects and makes dronedarone less lipophilic, shortening its half-life. Dronedarone has been shown to prevent atrial fibrillation/flutter (AF/AFl) recurrences in several multi-center trials. In addition to its rhythm control properties, dronedarone has rate control properties and slows the vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 59 publications
2
29
2
Order By: Relevance
“…As such, dronedarone may increase the bioavailability of other cardiovascular drugs including digoxin, simvastatin, and metropolol in some patients,10 and the pleiotropic effects of dronedarone may partly be due to effects on other drugs. Dosing of these drugs may need to be adjusted to prevent unwanted side effects 70. For example, it has been suggested that concomitant digoxin therapy contributed to the adverse outcomes with dronedarone in the PALLAS trial,22 and the combined use of both drugs is discouraged in the current guidelines 71…”
Section: Pleiotropic Actions Of Dronedaronementioning
confidence: 99%
“…As such, dronedarone may increase the bioavailability of other cardiovascular drugs including digoxin, simvastatin, and metropolol in some patients,10 and the pleiotropic effects of dronedarone may partly be due to effects on other drugs. Dosing of these drugs may need to be adjusted to prevent unwanted side effects 70. For example, it has been suggested that concomitant digoxin therapy contributed to the adverse outcomes with dronedarone in the PALLAS trial,22 and the combined use of both drugs is discouraged in the current guidelines 71…”
Section: Pleiotropic Actions Of Dronedaronementioning
confidence: 99%
“…In fact, amiodarone has been shown to cause time-dependent inhibition of CYP3A4 (Ohyama et al, 2000) and CYP2C8 (Polasek et al, 2004), a key feature of irreversible or quasi-irreversible inactivation of CYP450. Although dronedarone has been reported to be a moderate inhibitor of CYP3A4 and a weak inhibitor of CYP2D6 (Naccarelli et al, 2011), the potential inactivation of CYP450 by dronedarone and NDBD has not been investigated. In-house preliminary findings demonstrated that dronedarone inhibits CYP3A4 and CYP3A5 in a timedependent manner (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…While dronedarone can easily pass the blood-brain barrier [61], the mechanism(s) by which dronedarone exerts is neuroprotective function remain(s) to be elucidated but might relate to its acute inhibition of the sodium-calcium exchanger, potassium and/or sodium currents or the induction of HIF-1 (see above).…”
Section: Dronedarone In Cerebral Ischemia/reperfusionmentioning
confidence: 98%